Analisis Meta dengan Machine Learning: Tingkat Efektivitas Projectbased Learning untuk Meningkatkan Pemahaman Konsep Fisika - Sasikirana, Lituhayu; Fatin , Rahma Nabila; Setiaji , Bayu (Indonesian Journal Publisher, 2023)
This article proposes a meta-analysis using a quantitative approach to evaluate the effectiveness of Project-Based Learning (PjBL) in enhancing the understanding of physics concepts. By summarizing findings from 19 studies conducted in various countries, grade levels, and educational levels, this article aims to provide a comprehensive insight into the extent to which PjBL can be an effective learning approach. The analysis results reveal a diversity of effect sizes, with some studies indicating a positive impact and others indicating challenges in implementing PjBL. Moderator analysis highlights significant differences between studies conducted in Asia and Non-Asia, as well as at specific grade levels. Despite varying results, overall, PjBL can be considered effective in improving the understanding of physics concepts. By exploring recommendations and implications from this analysis, this article contributes to the development of the PjBL approach in the context of physics education in the future.